2013
DOI: 10.1176/appi.ps.201200144
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Criminal Justice Liaison and Diversion Services for Offenders With Mental Disorders: A Review

Abstract: Objective:The authors reviewed studies of the effectiveness of criminal justice liaison and diversion (CJLD) services in which outcomes of participants in these services were compared with those of offenders with mental illness who received no intervention or a standard intervention. The authors synthesized existing evidence with respect to changes in mental health status or criminal recidivism. Methods: A comprehensive search of more than 30 generic and specialist databases identified 6,571 published and unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…(Steadman, Redlich, Callahan, Robbins & Vesselinov, 2011). Evidence for the liaison and diversion model that is preferred in England and Wales (a model that does not explicitly include aspects of therapeutic jurisprudence) is, however, more limited (Scott, McGilloway, Dempster, Browne & Donnelly, 2013;Srivastava, Forrester, Davies & Nadkarni, 2013). Similarly, although diversion at an early point in the criminal justice pathway, from police custody, has been seen as necessary and achievable (Birmingham, 2001;James, 2010), the literature presently contains few descriptions of such services.…”
Section: Clinical Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Steadman, Redlich, Callahan, Robbins & Vesselinov, 2011). Evidence for the liaison and diversion model that is preferred in England and Wales (a model that does not explicitly include aspects of therapeutic jurisprudence) is, however, more limited (Scott, McGilloway, Dempster, Browne & Donnelly, 2013;Srivastava, Forrester, Davies & Nadkarni, 2013). Similarly, although diversion at an early point in the criminal justice pathway, from police custody, has been seen as necessary and achievable (Birmingham, 2001;James, 2010), the literature presently contains few descriptions of such services.…”
Section: Clinical Variablesmentioning
confidence: 99%
“…Despite their evidential limitations (Scott et al, 2013), there is presently a national intention to introduce and improve services for all people who present with mental health problems in the criminal justice systems using an all-age model which is focused on identifying cases through screening, with subsequent specialist assessment when it is required (NHSE, 2014a). Although these liaison and diversion services existed in England and Wales before the policy landscape shifted, albeit largely based in the lower (Magistrates') courts (James, 2006), the relatively recent priority that has been attached to their development has arisen from influential national policy reviews and subsequent Government responses (Bradley, 2009;Corston, 2007;Ministry of Justice, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of using CJLD services as a mechanism for accessing treatment is equivocal and appears to be model-dependent. Available evidence suggests that providing direct access to services and overseeing compliance through the CJS may be more successful than 'stand-alone' services such as that described here (Pakes & Winstone, 2010;Scott et al, 2013). However, this kind of approach would require an overhaul of many existing services (including the Belfast-based service) with attendant resource implications, whilst rigorous formative and summative research, such as that being undertaken currently (NHS England, 2014a) would also be required to inform such developments and evaluate the nature and extent of any change in outcomes over time.…”
Section: Conclusion Conclusion Conclusion Conclusionmentioning
confidence: 95%
“…In 2009, the Bradley review called for better support for people with mental health problems or learning difficulties throughout the criminal justice (CJ) system in England and Wales (Bradley, 2009) A recent systematic review found that L&D services did effectively identify offenders with mental health problems, improve psychosocial outcomes, for example substance use, quality of life, symptomatology and reduce days in prison/recidivism (Scott et al, 2013).…”
Section: Liaison and Diversion Mental Health Servicesmentioning
confidence: 99%